Pengembangan Unit Kegiatan Belajar Mandiri (UKBM) Materi Usaha dan Energi Berbasis Pembelajaran Kontekstual untuk Meningkatkan Pemahaman Konsep Siswa - Majid, M. Indra; Linuwih, Suharto (UPEJ Unnes Physics Education Journal, 2019)
One of the policies developed in the curriculum 2013 is to provide services to students according to their talents, interests, and learning abilities. A teacher is required to be able to provide an Independent Learning Activity Unit or Unit Kegiatan Belajar Mandiri (UKBM) for students. The goals of this research are to develop physics UKBM of work and energy based on contextual learning, to know the feasibility and readability of UKBM, and to know the improvement of student?s understanding about work and energy concepts. The used method in this research is Research and Development (R&D). The research steps consist of study of potential and problems, data collection, product design, expert validation, product revisions, small-scale trials, product revisions, and large-scale trials. One Group Pretest-posttest was used as the trials design. The subject of trials is 10th grade student of SMA Negeri 1 Kendal in 2018/2019 school year. The results of the research are the characteristics of UKBM of work and energy based on contextual learning according to the guidelines for developing UKBM and aspects of contextual learning. The core activities of the UKBM include four learning activities, which are the concept of work, the concept of the relationship of work and energy change, and the concept of the Law of Conservation of Mechanical Energy. The learning process was arranged using the Problem Based Learning model by presenting physics problems in daily life. UKBM of work and energy was declared very feasible with a percentage score of eligibility of 96%. The readability test result of 77% showed that UKBM was easy to understand. Based on the results of large-scale trials, the application of UKBM in learning can improve student's understanding of concepts with the gain of 0.49 in the middle improvement category.